Hla, anE. coliDNA-binding protein which accumulates in stationary phase, strongly compacts DNAin vitro - Annick Spassky; Sylvie Rimsky; Hervé Garreau; Henri Buc (1984)
We characterize a component of the E. coli bacterial nucleoid Hla, which accumulates in stationary phase. This protein, identical with the major component of a plasmid-protein complex previously isolated in our laboratory, has a p1 close to 7.5. Acrylamide gel electrophoresis and sedimentation in sucrose gradient have shown that the protein Hla induces significant compaction into DNA. This compaction is equivalent to that observed in nucleo some core although it introduces only a slight change in linking number. In addition, the structural change induced in the lactose L8UV5 promoter by Hla results in the decrease in the kinetic of formation of the open complex with RNA polymerase.